1994
DOI: 10.1002/macp.1994.021950235
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, properties and biodegradability of polyesters based on 1,3‐propanediol

Abstract: Aliphatic homopolyesters and copolyesters based on 1,3-propanediol and containing terephthalic acid as aromatic compound and sebacic acid as aliphatic compound were synthesized by condensation in bulk. Intrinsic viscosity and weight-average molecular weight were measured. Melting temperatures were studied by differential scanning calorimetry. For all polyesters the biodegradability was tested. Test media were inoculated with either municipal compost eluates or decanted sewage sludge. Criteria measured were vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(100 citation statements)
references
References 11 publications
1
97
0
2
Order By: Relevance
“…In contrast, non-degradable aromatic polyesters, such as PET exhibit much better physical and mechanical properties [2]. Recently, incorporation of aliphatic units into aromatic polyesters has been employed in improving the degradability of PET [3][4][5][6][7][8], poly (propylene terephthalate) (PPT) [3][4][5][6][7][8][9][10], poly(butylene terephthalate) (PBT) [8,[11][12], and poly(1,2-propanediyl phthalate) (PPP) [13]. Polylactic acid (PLA) is one of the widely used aliphatic polyesters, due to its environmentallyfriendly properties.…”
mentioning
confidence: 99%
“…In contrast, non-degradable aromatic polyesters, such as PET exhibit much better physical and mechanical properties [2]. Recently, incorporation of aliphatic units into aromatic polyesters has been employed in improving the degradability of PET [3][4][5][6][7][8], poly (propylene terephthalate) (PPT) [3][4][5][6][7][8][9][10], poly(butylene terephthalate) (PBT) [8,[11][12], and poly(1,2-propanediyl phthalate) (PPP) [13]. Polylactic acid (PLA) is one of the widely used aliphatic polyesters, due to its environmentallyfriendly properties.…”
mentioning
confidence: 99%
“…This fact has initiated an idea of combining the degradability of aliphatic polyesters and the superior mechanical properties of aromatic polyesters to achieve novel copolyesters. This concept has been employed in improving degradability of PET [4][5][6][7][8][9][10], poly(propylene terephthalate) (PPT) [10][11][12], Poly(butylene terephthalate) (PBT) [10,[13][14], and poly(1,2-propanediyl phthalate) (PPP) [15] by incorporating diols and/or diacids into their main chains. The results revealed that the degradation rate of the resulting copolymers was influenced by the content of aromatic constituents [10,13], chemical structures, i.e., random, block or alternating structure, solid state structure (semicrystalline or amorphous), and chain mobility [14].…”
mentioning
confidence: 99%
“…It is a complicated biochemical reaction process, in which the substrate and product are transported or diffused through the cell membrane, and a series of sequential and branched reaction are carried out by catalysis of enzymes in cells. 1 Many experiments and numerical simulations have been done for microbial fermentations, see Refs. 2-5 and the references therein.…”
Section: Introductionmentioning
confidence: 99%